PENDAMPINGAN PENYUSUNAN PETA DESA PAGERANDONG, KECAMATAN KALIGONDANG, KABUPATEN PURBALINGGA - Saputra, Aditya Saputra; Danardono, Danardono; Sunariya, M Iqbal Taufiqurrahman; Hussein, Stevie; Setiawan, Ilyas Nur; Farida, Rahma Afifah Nur (Universitas Muhammadiyah Surakarta, 2024)
Since the emergence of the Minister of Villages, Development of Disadvantaged Regions and Transmigration Regulation Number 4 of 2015 concerning the establishment, management, management and dissolution of Village-Owned Enterprises (BUMDES), villages have been indirectly given full authority to manage and develop their potential to become a successful village. independent with a high level of original village income. Each village will be allocated a certain amount of funds from the central government to be managed through BUMDES. Careful planning is needed to manage the potential and funds mandated by the central government. One of the first steps in planning is to map village boundaries. Many villages do not understand how to map village boundaries. Thus, assistance is needed, including outreach regarding village boundaries. Assistance in preparing the village map supports the preparation of the village master plan in the next process. The hope is that with this activity the village will be able to carry out village mapping and identify potential as a first step in preparing a master plan. The location chosen as the place of service is Pagerandong Village, Kaligondang District, Purbalingga Regency. Pagerandong Village has potential agricultural land that needs to be integrated into a thorough planning in the form of a master plan. Based on the results of the study and accompanying village maps, it is known that there are three main activities that have the potential to be developed, namely, agriculture with solar pump irrigation.